PEMILIHAN JENIS BIBIT UNGGUL TANAMAN NANAS DENGAN METODE ORESTE - Lisa Setia Ningsih; Riri Syafitri Lubis; Rima Aprilia (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
Indonesia is a country that has a tropical climate that is rich in fruits. One of the tropical fruit commodities in Indonesia is pineapple. Pineapple is most interest by public because price of the fruit is cheap, easy to obtain and has a distinctive aroma, taste, and color. Pineapple can be used as a medicinal plant. In the cultivation of pineapple plants, require the availability of good land and availability of seedlings that can be obtained in a vegetative and generative methods. Pineapple seeds obtained by generative means are fruit crowns, tiller shoots, root shoots, fruit shoots, stem cuttings. Meanwhile, pineapple seeds obtained by generative means are pineapple seeds. In pineapple cultivation carried out by pineapple farmers in Panribuan Village, Simalungun Regency, it is still based on farmer’s instincts and feelings, so that pineapple harvests often occur that are less than optimal, are not  resistant to pests, yields are less than optimal, harvest age becomes longer. With the alternatives that exist in the decision support system with the ORESTE method to select superior seeds of pineapple plants. A decision support system is one of the ways to organizing information  intended to be used in decisions  making. ORESTE is a method that was built for conditions where a set of alternatives will be sorted by criteria according to the levels of importance. From the calculation results obtained the best alternative is sapling shoots with the preference value of 1,547